Biofactories: new models for production and access to agricultural inputs in Latin America - Goulet, Frédéric; Guerrero Poveda, Daniela; Odjo, Sylvanus (Centre de Coopération Internationale en Recherche Agronomique pour le Développement, 2024)
The production and access to alternatives to chemical agricultural inputs are key issues today. In Latin America, solutions to these challenges (see Perspectives 55, May 2021) are becoming available thanks to the rise of biological inputs – including biofertilizers, biocontrol agents and biostimulants - resulting from many years of public investment in research and development, and a significant industrial drive in developing technologies based on micro-organisms, macro-organisms or plant extracts. However, the sector is taking a different route from the traditional agri-supply channels: NGOs, farmer networks, public policies and even some private stakeholders are encouraging the production of bio-inputs in bio-factories, directly on farms or in community facilities in rural areas. While these biofactories open up new prospects, they also face major challenges.